Detyrosinated Microtubules Modulate Mechanotransduction in Heart and Skeletal Muscle (2015)
ABSTRACT: In striated muscle, X-ROS is the mechanotransduction pathway by which mechanical stress transduced by the microtubule network elicits reactive oxygen species. X-ROS tunes Ca2+ signalling in healthy muscle, but in diseases such as Duchenne muscular dystrophy (DMD), microtubule alterations drive elevated X-ROS, disrupting Ca2+ homeostasis and impairing function. Here we show that detyrosination, a post-translational modification of α-tubulin, influences X-ROS signalling, contraction speed and cytoskeletal mechanics. In the mdx mouse model of DMD, the pharmacological reduction of detyrosination in vitro ablates aberrant X-ROS and Ca2+ signalling, and in vivo it protects against hallmarks of DMD, including workload-induced arrhythmias and contraction-induced injury in skeletal muscle. We conclude that detyrosinated microtubules increase cytoskeletal stiffness and mechanotransduction in striated muscle and that targeting this post-translational modification may have broad therapeutic potential in muscular dystrophies.